THE SITUATION OF ANTIBIOTIC TREATMENT OF COMMUNITY PNEUMONIA IN CHILDREN (Vietnam Journal of Community Medicine, 2021)
Objective: To investigate the situation of antibiotic use in the treatment of community pneumonia in children at Can Tho Children’s Hospital. Subjects and methods: Retrospective-descriptive study on 140 children diagnosed with community pneumonia, hospitalized for treatment at Can Tho Children’s Hospital from October 2020 to December 2020. Results: 55.71% of patients were taking antibiotics before hospitalization. Antibiotics used the most to treat pneumonia at hospital were penicillins/betalactamse inhibitors, accounting for 44.44%. For pneumonia patients, the rate of choosing the single regimen for initial treatment was 89.47% and the combination regimen was 10.53%. For patients with severe pneumonia, the rate of choosing of single regimen had decreased to 74.14%, while the choice of combination regimen had increased to 25.83%. The average number of regimen changes during treatment was 1.43 ± 056 times. The main reason for the change in the regimen was improved clinical symptoms (43.75%). The average duration of treatment with antibiotics was 6.48 ± 0.71 days. The duration of treatment as well as the duration of antibiotic use increased with the severity of the disease. Conclusion: The most commonly used antibiotics for treating commnity pneumonia at hospital were penicillins/betalactamse inhibitors. For pneumonia patients, a single regimen (89.47%) and a combination regimen (10.53%) was chosen. For patients with severe pneumonia, the choice of the single regimen decreased to 74.14%, the combination regimen increased to 25.83%. The main reason for the modification of the regimen was the improvement of clinical symptoms. The duration of treatment as well as the duration of antibiotic use increased with the severity of the disease.
Keywords: Pneumonia, children, antibiotics